A new genus and two new species of Galumnidae (Acari, Oribatida) from Nepal - Ermilov, Sergey G.; Martens, Jochen (Zootaxa, 2021)
One new genus and two new species of oribatid mites (Oribatida) of the family Galumnidae are described from soil in Nepal. Anomalogalumna gen. nov. (with type species Anomalogalumna dungeri sp. nov.) differs from Flagellozetes Balogh, 1970 by the absence of octotaxic system, and the presence of short, notogastral setae and areolate-reticulate surface of the notogaster and anogenital region. Allogalumna beateae sp. nov. differs from all other species of the genus by the presence of thickened rostral, lamellar and interlamellar setae, and the position of rostral seta (close to lamellar seta and distant from the rostrum).